Distinctive Characteristics of Its Principal Components - Arofatoy Muydinova (Academia One Publishing, 2023)
The article talks about Muvashshah poems of Muhammad Aminkhoja Muqimi, their specific features. Muvashshahs are important in studying the literary and aesthetic world of poets. Studying them on a scientific basis serves to a certain extent in illuminating the dark aspects of the history of literature
Keywords: poem; poet; verse